Editorial: Microbial safety of animal-based food products - Andrade, María J. (2025)
The studies gathered in this Research Topic focus on several key areas to ensure the safety of animal food products. Firstly, rapid pathogen detection is being improved through technologies like SWIR-HSI combined with advanced machine-learning techniques. Secondly, the use of natural antimicrobials, such as essential oils delivered via liposomes, is being explored to combat microbial development while minimizing negative impacts on food quality. Thirdly, investigations have revealed a link between high crayfish consumption and rhabdomyolysis, emphasizing the need to control the toxins in the food chain. Finally, studies on the relationship between diet and colorectal cancer have suggested a potential inverse association between high fish intake and risk of developing colorectal adenoma, suggesting a possible preventative role for fish consumption. These combined efforts aim to enhance the safety and quality of animal-derived foods through advanced detection methods, natural preservation strategies, and a broader understanding of foodborne threats.